Assessment of routine risk screening for predicting preterm birth at a public hospital in Thailand - Prateung Liampongsabudhi; Rajin Arora (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective:To assess the predictive value of the risk factors for preterm birth in public hospital.Materials and methods: Data of pregnant women who delivered in Lampang Regional Hospital from July 1, 2008 - June 30, 2010; were analyzed. Risk factors including history of preterm labor, uterine abnormality, hypertension, pregnant women who aged <20 years old, multifetal pregnancy and antepartum hemorrhage were evaluated. The diagnostic performance of establishment of at least one of six factors was calculated. Result: Among 7,435 pregnant women, 6.7% delivered preterm infants. Most of them were at GA 35-36 weeks of gestation (57.1%). Thirty one percent of these women had at least 1 of the 6 risk factors. The Odds ratio of preterm birth for was 2.41 (95% CI 1.96-2.95). Diagnostic performance showed sensitivity of 30.7%, specificity of 84.4%, positive predictive value of 12.5%, negative predictive value of 94.4%, likelihood ratio for positive test 1.98 and likelihood ratio for negative test of 0.82.Conclusion: Six factors of routine risk screening used in public hospital in Thailand had low screening performance and showed minimal benefit in clinical practices.